Globalization and National Resilience: Indonesia's Strategy for Maintaining National Stability - Hilmy Faishal Adhi; Emir Niam Anfaunnas (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2026)
Globalization has become a phenomenon that has driven major transformations in all aspects of national life, including economic, political, socio-cultural, and national security. In the Indonesian context, globalization presents significant opportunities such as technological advancement and economic growth, but also carries threats that can undermine national stability if not managed appropriately. This study aims to analyze the relationship between globalization and national resilience and formulate a comprehensive strategy for Indonesia to maintain national stability. The research method used was a literature review, examining 20 scientific articles published between 2020 and 2025. The results indicate that globalization influences national resilience through ideological, economic, socio-cultural, and digital security aspects. The research findings confirm that strengthening the Pancasila ideology, economic independence, digital literacy, cybersecurity, and cultural preservation are vital strategies for maintaining national resilience. The study's conclusions indicate that Indonesia's national resilience can only be maintained if the government, society, and education sector work together to address global challenges adaptively and sustainably.